A COMPARATIVE STUDY OF LATERALIZED TRANSVERSE INCISION APPENDECTOMY VERSUS LAPAROSCOPIC APPENDECTOMY - MAHNA, ABHISHEK (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of this study were to compare the effectiveness of lateral transverse cosmetic incision (LTCI) versus laparoscopic appendectomy in terms of operative and post-operative parameters. Methods: One hundred and forty patients who were admitted after the diagnosis of appendicitis were divided into two groups of 70 each. Patients in Group A were treated by lateralized transverse incision appendectomy, while Group B patients underwent laparoscopic appendectomy. Results: In the present study, male: female ratio was found to be 2:1 with majority of the patients belonging to age group of 21–50 years (75.72%). Post-operative hospital stay in Group A patients was 2±0.68 days in comparison to 2±0.75 days in laparoscopy group which was comparable. Duration of surgery in minutes in Group A was 46±18.65 while in Group B, it was 91±17.75 with a significant P ≤ 0.0001. The cost of surgery was Rs.3200±450 in LTCI, while it was Rs.4200±600 in laparoscopic group with P < 0.0001 which was found to be highly significant. Conclusion: Lateral transverse incision appendectomy was found to be as effective as laparoscopic appendectomy. The method is a preferred procedure, particularly in those set ups where the advanced equipments and specially trained doctors and technicians are not available. In the present study, lateral transverse technique was found to be safe, cosmetically much better, and without mortality and negligible morbidity. Furthermore, less hospital stay, less need for analgesics, less need for skilled personnel, early return to the routine, less surgery duration, and less expensive as compared to laparoscopic surgery make the conventional method equally preferable.